Co-existent breast and renal cancer - Üreyen, Orhan (Ulus Cerrahi Derg, 2015)
The concomitant presence of breast cancer with one or more other types of cancer such as colon, vulva, lung, larynx, liver, uterus and kidneys has been presented in the literature. However, synchronous breast and renal cancer is very uncommon. Herein we present a woman with synchronous breast and renal cancer, and review the literature. A 77-year-old post-menopausal woman was admitted to our clinic complaining of left sided breast mass. On physical examination, there was a 3 cm palpable mass in the upper outer quadrant of the left breast along with a conglomerate of lymph nodes in the left axilla. Ultrasonography and mammography showed a 3 cm solid, hypoechoic mass in the upper outer quadrant and left axillary lymphadenopathy. The tru-cut biopsy of the lesion revealed invasive ductal carcinoma. The bone scintigraphy, thoracic and cranial computerized tomographies were normal. The abdominal computerized tomography identified a 3×3 cm solid renal mass with heterogeneous contrast enhancement in the posterior segment of the lower pole, which was suspicious for renal cell carcinoma. Breast conserving surgery and axillary lymph node dissection was performed, and the pathology specimen demonstrated invasive ductal carcinoma. The patient was discharged on postoperative day 5. Three weeks later partial nephrectomy was performed by urology department for the solid renal mass, and the pathology result showed clear cell-renal carcinoma with Fuhrman grade 3. The patient is being followed-up for renal carcinoma, and underwent radiotherapy for breast cancer. Hormonotherapy for breast cancer is still continuing.